Symbolated texts as an assistive technology: Exploring the impact on reading comprehension - Benson-Goldberg, Sofia (Research in developmental disabilities, 2025)
It is widely assumed that pairing graphic symbols with text supports individuals with intellectual and developmental disabilities (IDD) in accessing written content. As a result, these symbolated texts are often used as an assistive technology to increase text accessibility. Unfortunately, there is little empirical evidence that symbolated texts improve reading comprehension. Research with beginning and struggling readers suggests that pairing text with any type of image makes understanding text more difficult and impedes reading growth by distracting individuals’ visual attention away from the text on the page. Despite this, there continues to be widespread use of symbolated texts. The purpose of this study was to investigate the impact of symbolated text on the reading comprehension of individuals with IDD. Objective measures of reading comprehension and reading-level matched texts with and without graphic symbols were used to: (a) compare comprehension scores across text-type; (b) investigate the impact of symbols on reading rate; and (c) look for relationships between reading rate and reading comprehension scores. Results suggest that reading comprehension scores are significantly lower for symbolated texts than traditional texts. Additionally, pairing graphic symbols with text resulted in significantly slower reading times. The findings suggest that symbolated texts may not make texts more accessible for individuals with IDD. Rather, they may actually make content less accessible. Anyone producing texts for this population should be cautious about pairing graphic symbols with text. •Pairing graphic symbols with text is a common assistive technology used to make texts more accessible to individuals with IDD.•In this study adding graphic symbols to text did not make them easier to read.•Participants did worse when reading symbolated texts.•Pairing graphic symbols with text should not be assumed to make texts easier to read.•Other modifications to text should be considered instead of adding graphic symbols to text.